CLOUD COMPUTING AND GENERATIVE AI: TRANSFORMING CRM ACROSS INDUSTRIES - Chandrasena Cheerla (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This technical article examines the transformative impact of cloud computing and generative artificial intelligence (AI) on Customer Relationship Management (CRM) systems across diverse industries. Integrating these technologies fundamentally reshapes customer engagement strategies, enabling organizations to achieve unprecedented levels of personalization, automation, and service delivery optimization. This article comprehensively analyzes the core technological frameworks, implementation methodologies, industry-specific applications, and strategic benefits of combining cloud infrastructure with generative AI capabilities in modern CRM systems. This article explores how this technological convergence drives operational excellence, enhances customer experiences, and creates sustainable competitive advantages across retail, financial services, healthcare, and manufacturing sectors.